The factorial structure of professionally-applied physical fitness of students of railway specialties - Anzhelika Yefremova; Lydmyla Shesterova (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to define the factorial structure of professionally-applied physical fitness of students - future electrical engineers of railway transport. Material & Methods: analysis and synthesis of references, questioning, anthropometry, testing, functional tests, and methods of mathematical statistics (the factorial analysis) with application of the computer program "SPSS 17.0". 50 students (young men) of Ukrainian state railway university participated in the research. Results: the ratio of means of physical culture which are expedient to use for the optimization of professionally-applied physical training of future specialists of the railway branch is defined. Conclusions: the factorial analysis allowed to distribute means of physical education as follows: physical exercises which are directed to the increase in physical working capacity and overall physical fitness - about 40%; exercises on the development of power qualities - 25%; exercises on the development of high-speed and power endurance - 15%; means which are allocated for the improvement of functions of attention and kinetic sensitivity - 10%; exercises which are directed to the increase in special working capacity - 10%.